Kondo physics of magnetic adatoms on metallic surfaces when the onset of the surface conduction density of states crosses the Fermi level - Fernández, Joaquín (2019)
We study the role of the onset of Shockley states Ds belonging to (111) surfaces of Cu, Ag, and Au in the Kondo effect when a magnetic impurity is deposited on them. When Ds approaches the Fermi level EF, which can be done by compressing (stretching) the metallic sample, we find that most of the thermodynamic and dynamic properties of the impurity are affected in a nontrivial way. We model the system by a generic Anderson impurity model and solve it by using the numerical renormalization group technique. In particular, the impurity contribution to magnetic susceptibility and entropy as a function of temperature exhibit negative values and go to zero slowly in a logarithmic shape. Furthermore, we found suppression of the spectral density weight at the Fermi level when Ds∼EF even in the Kondo regime. As a consequence, the conductance through the impurity is strongly reduced by nearly 25% of the unitary value 2e2/h. Finally, we analyze these features in realistic systems like Co on Ag(111) reported in the literature.